Carbon uptake bioenergetics of PAOs and GAOs in full-scale enhanced biological phosphorus removal systems. (1st June 2022) - Chen, Liping; Chen, Hang; Hu, Zekun; Tian, Yucheng; Wang, Cenchao; Xie, Peiran; Deng, Xuhan; Zhang, Yushen; Tang, Xia; Lin, Xueran; Li, Biqing; Wei, Chaohai; et al.
Highlight: PAOs and GAOs showed major differences in carbon uptake bioenergetics. GAOs intensively employed the fumarate reductase (Frd) pathway. PAOs rarely activated Frd or F1, F0-ATPase for acetate or propionate uptake. Amino acid uptake by PAOs involved high Frd and F1, F0-ATPase activities. The major differences made possible for selective inhibition of GAOs. Abstract: This work analyzed, for the first time, the bioenergetics of PAOs and GAOs in full-scale wastewater treatment plants (WWTPs) for the uptake of different carbon sources. Fifteen samples were collected from five full-scale WWTPs. Predominance of different PAOs, i.e., Ca. Accumulibacter (0.00–0.49%), Tetrasphaera (0.37–3.94%), Microlunatus phosphovorus (0.01–0.18%), etc., and GAOs, i.e., Ca. Competibacter (0.08–5.39%), Defluviicoccus (0.05–5.34%), Micropruina (0.17–1.87%), etc., were shown by 16S rRNA gene amplicon sequencing. Despite the distinct PAO/GAO community compositions in different samples, proton motive force (PMF) was found as the key driving force (up to 90.1%) for the uptake of volatile fatty acids (VFAs, acetate and propionate) and amino acids (glutamate and aspartate) by both GAOs and PAOs at the community level, contrasting the previous understanding that Defluviicoccus have a low demand of PMF for acetate uptake. For the uptake of acetate or propionate, PAOs rarely activated F1, F0- ATPase (< 11.7%) or fumarate reductase (< 5.3%) for PMF generation; whereas, intensive involvements of these two pathways (up to 49.2% and 61.0%, respectively) were observed for GAOs, highlighting a major and community-level difference in their VFA uptake biogenetics in full-scale systems. However, different from VFAs, the uptake of glutamate and aspartate by both PAOs and GAOs commonly involved fumarate reductase and F1, F0-ATPase activities. Apart from these major and community-level differences, high level fine-scale micro-diversity in carbon uptake bioenergetics was observed within PAO and GAO lineages, probably resulting from their versatilities in employing different pathways for reducing power generation. Ca. Accumulibacter and Halomonas seemed to show higher dependency on the reverse operation of F1, F0-ATPase than other PAOs, likely due to the low involvement of glyoxylate shunt pathway. Unlike Tetrasphaera, but similar to Ca. Accumulibacter, Microlunatus phosphovorus took up glutamate and aspartate via the proton/glutamate-aspartate symporter driven by PMF. This feature was testified using a pure culture of Microlunatus phosphovorus stain NM-1. The major difference between PAOs and GAOs highlights the potential to selectively suppress GAOs for community regulation in EBPR systems. The finer-scale carbon uptake bioenergetics of PAOs or GAOs from different lineages benefits in understanding their interactions in community assembly in complex environment. Graphical abstract: Image, graphical abstract